2020
DOI: 10.22460/project.v3i4.p512-517
|View full text |Cite
|
Sign up to set email alerts
|

Flouting Maxims on the Dialogue of Characters in Up! Animated Movie

Abstract: This research is about flouting maxims on the dialogue of characters in UP! Animated movie. Hence, it is aimed to know flouting maxim on  UP! animated movie. This research is used qualitative research. The data of this study was taken on flouting maxims on the discourse of figure in UP! animated movie from he main characters namely old name Carl Fredrickson and Russel. There are several steps in collecting the data namely, finding a script UP! of the animated movie, next is analyzing the script with the UP! mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It is a condition when there is something irrelevant to answering the previous conversation. It makes the interlocutor confused and cannot catch the message of the communication (Giriyani & Efransyah, 2020). From the movie, it can be seen that there is a flouting maxim of relevance found.…”
Section: Anddiscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a condition when there is something irrelevant to answering the previous conversation. It makes the interlocutor confused and cannot catch the message of the communication (Giriyani & Efransyah, 2020). From the movie, it can be seen that there is a flouting maxim of relevance found.…”
Section: Anddiscussionmentioning
confidence: 99%
“…For example, flouting the maxim of quantity occurs when the speaker tells very little or too much information in the conversation. A study by Giriyani & Efransyah (2020) shows the flouting of four maxims in an animated movie entitled UP! They find that in flouting the maxim of quantity, the movie images it through the inconsistency and repeated sentences to be said at one time by the characters.…”
Section: Cooperative Principle and Flouting Maximmentioning
confidence: 99%
See 1 more Smart Citation
“…The episode group encompasses a typical story. Past research has investigated the CP as it is observed, or not observed, by characters in various television series (Giriyani & Efransyah, 2020;Sapalakkai, 2018;Sommai, 2013). However, only a small amount of research has focused on one particular maxim (Khosravizadeh & Sadehvandi, 2011) performed, in this case, by a character playing the role of an autistic doctor.…”
mentioning
confidence: 99%